Analisis Pengaruh Jumlah Jam Orang (Man Hour) terhadap Tingkat Produktivitas Galangan Kapal di Surabaya - Muh. Adrian Ariq Maulana; Minto Basuki (Ocean Engineering : Jurnal Ilmu Teknik dan Teknologi Maritim, 2023)
In a shipbuilding industry, fast and efficient time is needed in carrying out construction projects and ship repairs. This is because it has been mutually agreed between the two parties, both the owner of the ship (owner), and the shipyard regarding the time to work on the project. By racing on the processing time, the level of productivity is an important point that must be considered by the shipyard. There are many factors that can affect the level of productivity of a shipyard. One of the factors, among others, is the determination of the number of man hours (man hours). In a ship building or repair project, the allocation of the number of man hours is very important, if the number of man hours (man hours) is not correct it will cause delays and decrease in productivity levels. The purpose of this study was to analyze the effect of man hours on the level of productivity in the KMP repair project. Cakalang and KMP. Gili Iyang by conducting a correlation test of the Product Moment method with the help of SPSS (Statistical Program for Social Science) v2.3 for windows software, with the independent variable (X), namely the number of man hours (man hours) and the dependent variable (Y), namely the level of productivity. And then a significant correlation value is generated between the number of man hours (man hours) and the level of shipyard productivity. The results of this study are the significance values obtained between the X and Y variables in the KMP repair project. Cakalang is 0.037 and at KMP. Gili Iyang is 0.026 which means that there is a significant correlation between the variable man hours and productivity with a very strong relationship category in KMP. Cakalang and strong links to KMP. Gili Iyang.